The development and assessment of the Worry About Pain Questionnaire. (23rd February 2017) - Lefebvre, J.C.; Jensen, M.P.; Waters, S.J.; Molton, I.R.; Keefe, F.J.; Caldwell, D.S.
Abstract: Background: Worry can be conceptualized as a cognitive–affective automatic process initiated in order to address uncertainty and potential personal inadequacies that could result in negative outcomes. The purpose of the current study was to develop a measure of pain‐specific worry – the Worry About Pain Questionnaire (WAPQ). Method: In study 1, responses of 335 pain‐free participants were used to complete an item analysis and exploratory factors analysis to develop and assess the internal structure of the WAPQ. Study 2 included 224 pain‐free participants who completed the WAPQ in order to confirm its factor structure, and to examine its relation to the experience of acute experimental pain. In study 3, 137 individuals with persistent pain were asked to complete the WAPQ as well as measures of pain and depressive symptoms. Results: The resulting 15‐item measure assesses uncertainties and potential negative outcomes related to the experience of pain. The results of the exploratory and confirmatory factor analyses showed a two‐factor structure. Across all studies, the WAPQ was found to be related to measures of pain in clinical and non‐clinical samples, acute experimental pain stimuli, as well as pain anxiety, pain catastrophizing, fear of pain, rumination and depressive symptomatology. Conclusions: The results suggest that the WAPQ is a reliable and valid measure for the assessment of worry about pain that can be used to understand how pain‐specific worries are related to the experience and impact of pain across different populations. Significance: Worry has been assessed in pain populations using measures that assess worry in general. The current study shows a relationship between pain‐specific worry and the experience of pain. Further, worry about pain is related to but not synonymous with pain catastrophizing.